General molten-salt route to three-dimensional porous transition metal nitrides as sensitive and stable Raman substrates - Haomin Guan (Nature Portfolio, 2021)
Fabrication of transition metal nitrides generally requires harsh conditions due to the high activation energy barrier for nucleation. Here, the authors report a mild molten-salt route for the synthesis of three-dimensional porous metal nitrides, VN, MoN, WN, and TiN.